2020
DOI: 10.1038/s41598-020-67195-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolome and cognitive skills in Down syndrome

Abstract: Trisomy 21 (Down syndrome, DS) is the main human genetic cause of intellectual disability (ID). Lejeune hypothesized that DS could be considered a metabolic disease, and we found that subjects with DS have a specific plasma and urinary metabolomic profile. In this work we confirmed the alteration of mitochondrial metabolism in DS and also investigated if metabolite levels are related to cognitive aspects of DS. We analyzed the metabolomic profiles of plasma samples from 129 subjects with DS and 46 healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…In 50 of 77 subjects evaluated by Griffiths-III and WPPSI-III tests (see Methods section), several other metabolites were already analyzed with 1 H-Nuclear Magnetic Resonance (H-NMR) in Antonaros et al 31 , but none of them showed a correlation with IQ scores. These data suggest that metabolites analyzed in the present work could have a crucial role in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In 50 of 77 subjects evaluated by Griffiths-III and WPPSI-III tests (see Methods section), several other metabolites were already analyzed with 1 H-Nuclear Magnetic Resonance (H-NMR) in Antonaros et al 31 , but none of them showed a correlation with IQ scores. These data suggest that metabolites analyzed in the present work could have a crucial role in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Caracausi et al ( 2018 ) and Antonaros et al ( 2020 ) reported raw data values. M, SD, and N were calculated for each compound both in DS and in control groups, as well as in plasma and in urine samples while the fasting condition was not considered.…”
Section: Gene Expression Proteomic and Metabolomic Profiling Of Ds Amentioning
confidence: 99%
“…” section). The fundamental role of metabolic and bioenergetic alterations in DS have been suspected for over 70 years and has periodically re-emerged as a working hypothesis (Simon et al 1954 ; Anon 1954 ; Breg 1977 ; Shapiro 1983 ; Blass et al 1988 ; Lejeune 1990 ; Chango et al 2002 ; CoppedĂš 2009 ; Izzo et al 2018 ; Vacca et al 2019 ; Antonaros et al 2020 ). Jerome LeJeune, the French physician-scientist, who discovered the chromosome abnormality in humans that causes DS, constructed a “Lejeune Machine” (Lejeune 1990 ), to illustrate the biochemical and metabolic alterations associated with this condition.…”
Section: Down Syndrome As a Metabolic Disease: An Introductionmentioning
confidence: 99%
“…One of the main findings of metabolomics is that systemic biofluids like blood, urine and saliva, contain a strong individual metabolic signature, called metabolic phenotype or metabotype, which is stable over time, allowing us to monitor individual status and response to different stimuli [ 22 , 23 , 24 , 25 , 26 , 27 ], as well as to fingerprint several different diseases [ 28 , 29 , 30 , 31 , 32 , 33 ]. The metabotype is a multifactorial entity; in fact, besides being a snapshot of the subject’s genotype and metabolism, it is also influenced by many other factors, like gut microbiota, diet, lifestyle, drugs, etc.…”
Section: Introductionmentioning
confidence: 99%